Peran Pajak dalam Meningkatkan Pembangunan Pendidikan di SMKN 7 Tangerang - Widya Astuti; Ananda Putriani (Journal on Education, 2023)
This study aims to analyze the role of taxes in increasing educational development at SMKN 7 Tangerang. The method used in this research is qualitative descriptive analysis. The approach taken is by analyzing the results of the interviews that have been conducted and then describing them. Qualitative research is research that produces descriptive data in the form of written or spoken words. The data taken was obtained from a question and answer session with resource persons, relevant sources, as well as direct visits to SMKN 7 Tangerang. The data analysis technique used in this research is qualitative content analysis. The results of this study indicate that taxes play an important role in improving educational development such as facilities, teaching staff, and developing the potential of students at SMKN 7 Tangerang. Taxes play a role in providing assistance in the form of physical and non-physical. Taxes play a role in improving school facilities. Taxes play a role in managing funds provided by the government. Based on the results of this study, it was concluded that public schools receive subsidized assistance from the government, the assistance provided is obtained from public awareness in paying taxes.